The Cause of Urban Slang and its Effect on the Development of the Northern Sotho Lexicon - Mojela, V.M. (Lexikos, 2002)
Abstract: Urban slang terminology is extensively used today by most indigenous communities when speaking various South African indigenous languages. This is usually the case with informal conversations where the type of language used is also regarded to be informal. There are many instances where slang terms are used, consciously or unconsciously, in the form of code-switching with the indigenous languages in formal speech or informal conversations. These urban slang terms are regarded by most of the South African indigenous communities as prestige terms, especially by the young generation. Just as English and Afrikaans terminologies which had tremendous influence on the vocabularies of the indigenous languages, urban slang terminology has great influence on the daily usage of the South African indigenous languages. Despite this pressure, Northern Sotho and other South African indigenous languages do not have officially recognized adoptives which are derived from slang terminology. This is due to the fact that most language authorities do not want to associate their standard languages with urban slang because of various reasons which include, inter alia, the conservative idea of associating urban slang with crime and juvenile delinquency. Despite the negative attitudes of most of the conservative language authorities who regard the loan words of urban slang origin to be "contaminating" the South African indigenous languages (such as Northern Sotho), this slang terminology is every day becoming more popular and seems to have come to stay rather than be removed from the language of the people. A considerable fraction of the vocabulary of Northern Sotho, for instance, is made up of words which can be regarded as "loan words" derived from urban slang, even though formally we are still refusing to accept them as part of the lexicon of official Northern Sotho. Keywords: EUPHEMISM, FLYTAAL, INFERIOR DIALECT, INFERIOR LANGUAGE, MULTILINGUALISM, NORTHERN SOTHO LEXICON, PRESTIGE LANGUAGE, PRESTIGE TERMINOLOGY, SECRET TERMINOLOGY, TSOTSITAAL, URBAN SLANG, UNDERWORLD Opsomming: Die oorsprong van stedelike sleng en die uitwerking daarvanop die ontwikkeling van die Noord-Sotholeksikon. Stedelike slengterminologieword tans wyd gebruik deur die meeste inheemse gemeenskappe wanneer hulle verskillendeinheemse Suid-Afrikaanse tale praat. Dit is gewoonlik die geval met informele gesprekke waar die gebruikte tipe taal ook as informeel beskou word. Daar is baie gevalle waar slengterme, bewustelikof onbewustelik, gebruik word in die vorm van kodewisseling met die inheemse tale in formelespraak of informele gesprekke. Hierdie stedelike slengterme word as prestigeterme deur die meestevan die inheemse Suid-Afrikaanse gemeenskappe, veral deur die jong generasie beskou. Netsoos Engelse en Afrikaanse terminologieë wat groot invloed op die woordeskat van die inheemsetale gehad het, het stedelike slengterminologie ’n groot invloed op die daaglikse gebruik van dieinheemse Suid-Afrikaanse tale. Ten spyte van hierdie druk het Noord-Sotho en ander inheemseSuid-Afrikaanse tale nie amptelik erkende leenwoorde wat van slengterminologie afgelei is nie. Ditis die gevolg van die feit dat die meeste taaloutoriteite nie hul standaardtale geassosieer wil hê metstedelike sleng nie, vanweë verskillende redes wat, onder andere, die konserwatiewe idee van dieassosiasie van stedelike sleng met misdaad en jeugmisdaad insluit. Ten spyte van die negatiewehoudings van die meeste konserwatiewe taaloutoriteite wat die leenwoorde van stedelikeslengoorsprongbeskou as "kontaminerend" vir die inheemse Suid-Afrikaanse tale (soos Noord-Sotho),word hierdie slengterminologie elke dag meer populêr en lyk dit of dit blywend is eerder as verwyderbaaruit die taal van die mense. ’n Aansienlike deel van die woordeskat van Noord-Sotho,byvoorbeeld, bestaan uit woorde wat beskou kan word as "leenwoorde" verkry uit stedelike sleng,alhoewel ons nog formeel weier om hulle as deel van die leksikon van offisiële Noord-Sotho teaanvaar. Sleutelwoorde: EUFEMISME, FLAAITAAL, ONDERGESKIKTE DIALEK, ONDERGESKIKTE TAAL, MEERTALIGHEID, NOORD-SOTHOLEKSIKON, PRESTIGETAAL, PRESTIGETERMINOLOGIE, GEHEIME TERMINOLOGIE, TSOTSITAAL, STEDELIKE SLENG, ONDERW?- RELD